The storage stability and concentration of acetoacetate differs between blood fractions. - McNeil, C; Pramfalk, C; Humphreys, S; Hodson, L (Elsevier, 2014)
BACKGROUND: Plasma concentrations of 3-hydroxybutyrate (3HB) are measured more often than acetoacetate (AcAc) which may be due to the reported storage instability of AcAc. The aims of the study were to compare the storage stability of AcAc in different blood fractions over time (90days) when stored at -80°C and to determine the postprandial concentration of AcAc in whole blood, plasma and red blood cells. METHODS: Blood was collected from fasting subjects (n=5): whole blood, plasma and red blood cells were isolated and deproteinised in perchloric acid, and supernatants were stored at -80°C until analysis. Postprandial concentrations of AcAc in whole blood, plasma and red blood cells were determined at regular intervals over 420min, after subjects (n=23) had consumed a mixed test meal. RESULTS: Storing deproteinised plasma at -80°C resulted in no significant change in AcAc concentration over 60days. In contrast, whole blood AcAc concentrations significantly decreased by 51% (p=0.018) within 30days. The concentration of AcAc in fasting and postprandial plasma was notably higher than that of whole blood and red blood cells. DISCUSSION: Our data demonstrates that plasma for AcAc analysis can be stored for longer than previously suggested provided that plasma is deproteinised and stored at -80°C.